Heteroplasmic substitutions in the entire mitochondrial genomes of human colon cells detected by ultra-deep 454 sequencing. (March 2015) - Skonieczna, Katarzyna; Malyarchuk, Boris; Jawień, Arkadiusz; Marszałek, Andrzej; Banaszkiewicz, Zbigniew; Jarmocik, Paweł; Borcz, Marcelina; Bała, Piotr; Grzybowski, Tomasz
Highlights: We compared the ability of 454 and dideoxy methods to detect point heteroplasmy. Minority variants above the 2% level were found in one third of the population. Heteroplasmic substitutions were localized at different positions in mtDNA. Majority of heteroplasmic substitutions hit positions observed in human mtDNA tree. Abstract: Mitochondrial DNA (mtDNA) heteroplasmy has been widely described from clinical, evolutionary and analytical points of view. Historically, the majority of studies have been based on Sanger sequencing. However, next-generation sequencing technologies are now being used for heteroplasmy analysis. Ultra-deep sequencing approaches provide increased sensitivity for detecting minority variants. However, a phylogenetic a posteriori analysis revealed that most of the next-generation sequencing data published to date suffers from shortcomings. Because implementation of new technologies in clinical, population, or forensic studies requires proper verification, in this paper we present a direct comparison of ultra-deep 454 and Sanger sequencing for the detection of heteroplasmy in complete mitochondrial genomes of normal colon cells. The spectrum of heteroplasmic mutations is discussed against the background of mitochondrial DNA variability in human populations.